WAQF CONTRACT MANAGEMENT IN EMPOWERING AR-RAHMAN MOSQUE IN BLITAR CITY - Ningtyas, Dwi Wahyu; Nabawy, Nuhan; Syayidah, Laily Nur; Toyibah, Askin (Yayasan Education and Social Center, 2023)
This research is motivated by the viral Ar-Rahman mosque which is a miniature of the Nabawi Mosque in Medina and as an Islamic Center in Blitar City. The Ar-Rahman Mosque is a mosque built on waqf land covering an area of 2,806 square meters which is estimated to be able to accommodate 1,000 worshipers. The mosque was built with architecture like the Nabawi Mosque of Medina starting from the interior, green dome, building height, to the umbrella ornament of the mosque courtyard. This study aims to determine the management of waqf contracts carried out at the Ar-Rahman Mosque. The method used is descriptive qualitative. The data collection techniques were conducted through interviews, observation, and documentation. In-depth interviews were conducted with the head of Mayangkara Group, Mr. Harianto, HR department, management department, mosque takmir, donors, finance department, security guard, clining service, imam, health department, HEC mosque manager, muadzin, and consumption department. The result of this research is that the management of waqf management at the Ar-Rahman Mosque is quite good. The waqf land has been certified so that it does not endanger the waqf property in the future. The quality of human resources of mosque managers is also good but needs to be improved in order to manage waqf assets more productively. Most mosque managers only run religious and social programs and have not developed waqf assets in a more productive direction